Analisis Pemilihan Serentak Kepala Daerah 2024 Dalam Perspektif Negara Hukum Indonesia - Muslih, Muhammad; Somad, Kemas Abdul; Saputra, Warfian (Wajah Hukum, 2023)
Simultaneous regional head elections, if seen at a glance, are a solution to the non-ideal nature of holding relatively large and repeated regional head elections, but if we look closely we can still discuss in detail the negative side of this policy. This is because there are some regional heads whose term of office must be reduced, thereby contradicting several legal norms (UU). In order to explore and discuss this problem, this paper uses a library research method with a conceptual and statutory approach, while the analysis is qualitative. The theory or teachings used as an analytical tool are theories, teachings about the concept of the rule of law. From several findings, it turns out that the policy of simultaneously electing regional heads has the potential to violate human rights and what is certain is that de facto regional heads whose terms of office have been reduced have been disadvantaged, treated unequally to other regional heads, thus the policy of simultaneously electing regional heads is not directly proportional to the enthusiasm and spirit of regional heads constitution.